Bis(4-methylpiperidinyl)-phenylphosphine and bis(4-benzylpiperidinyl)-phenylphosphine: Synthesis, derivatization, molybdenum complexes and DFT calculations - Sarioz, Ozlem; Kandemirli, Fatma; Oznergiz, Sena (Elsevier BV, 2014)
Abstract Functionalized bis(amino)phosphines of the type PhP(NR2)2 have been synthesized by treating PhPCl2 with 4-methylpiperidine or 4-benzylpiperidine. The ligands react with aqueous hydrogen peroxide, elemental sulfur or selenium to give the corresponding chalcogenides in good yield. The molybdenum complexes of the bis(amino)phosphines have been obtained. All of the compounds were obtained in good yields and were characterized by IR, NMR and elemental analysis. Quantum chemical calculations, such as HOMO–LUMO energies, Mulliken charges etc., were carried out using B3LYP/6-31G(d,p), a version of the DFT method with the standard gaussian 09 software package program for the bis(amino)phosphines and their chalcogenides. The experimental and theoretical results show that PPh(NC5H9CH3)2 (1) and PPh(NC5H9CH2C6H5)2 (2) are strong σ-donors and have similar electronic properties.
Keywords: Aminophosphines; Aminophosphine chalcogenides; Quantum chemical calculations; Aminophosphine complexes; DFT; 3. Good health